Human and economic geography - Leong, Goh Leong; Morgan, Gillian C. (Hong Kong : Oxford university press, 1999)
An ideal reference book for A Level students.Much emphasis has been placed on conditions and problems in developing countries and wherever possible regional examples have been quoted to illustrate general points. At the same time a world-wide coverage has been maintained to allow students to compare between developing and advanced countries.
Includes index
Keywords: Economic geography -- Textbooks; Human geography -- Textbooks